The role of civil society organisations in promoting democratic process in Zimbabwe 1980-2013 - Mwaradzika, Marceline L. (Midlands State University, 2017)
This dissertation focuses mainly on the role of Civil Society Organizations in promoting democratic process in Zimbabwe as of 1980-2013. Civil Society is an umbrella organization which consists of many sub sectors as follows nongovernmental organizations, private sector organisation, labour unions, women’s groups, professional associations, religious groups, the marginalized masses, media organizations and other informal groups like cultural and economic groups. In this study the researcher aimed at assessing the role of these Civil Societies in the issues of democracy, their relationship status with the government of Zimbabwe, also examining the draconian laws endorsed by the government to curb the activities of the civil societies and their impacts and also to focus on human rights because there is no way one can manage to talk about democracy without human rights involved. Good Governance is the participation of a variety of groups other than the leading elites in decision making. Democracy is a system of governance in which leaders are held responsible for their deeds, in the civic dominion by populace, acting indirectly through the opposition and collaboration of their elected representatives. Totalitarianism in Zimbabwe has history. Historically, Zimbabwe is more common with absolutism than democracy. In addition Zimbabwe has only known democracy in its ordinary sense. This kind of authoritarianism can be traced back to the colonial period originated more than a century ago. Authoritarianism was not only a central propensity during colonial period but was part of the luggage inherited by the Zimbabwean leaders in 1980.